Calculation of the Kinetic Parameters of the Hydrofining Process of Diesel Fraction Using Mathematical Modeling - Krivtsova N. I. Nadezhda Igorevna; Tataurshchikov A. A. Anton Andreevich; Ivanchina E. D. Emilia Dmitrievna; Krivtsov E. B. Evgeny Borisovich; Golovko A. K. Anatoly Kuzmich (2015, 2015)
Title screen